Thymic carcinoma presenting as atypical chest pain. (25th November 2015) - Siddiqui, Sadiq; Connelly, Tara; Keita, Luther; Blazkova, Sylvie; Veerasingam, Dave
Abstract : A 58-year-old woman with a 2-month history of atypical chest pain was referred to the chest pain clinic by the general practitioner. Exercise stress test was positive and subsequent coronary angiogram revealed significant triple vessel disease with left ventricular impairment requiring a coronary artery bypass graft (CABG). The patient had a chest X-ray as part of the preoperative work up. Chest X-ray revealed a large anterior mediastinal mass. Subsequent thorax CT revealed a 7.2  cm anterior mediastinal mass. CT-guided biopsy of the mass revealed the diagnosis of a poorly differentiated thymic basaloid carcinoma. The patient was successfully treated with concomitant surgery involving complete resection of the mass and a CABG procedure.